Differences of Basic School Students' Network Results in the Implementation of STAD Type Cooperative Learning Models Aided by Animation Media and Power Point Media in the Plant Subtemes of My Friends from Learning Activities - Arnida Suryani; Ajat Sudrajat; Amalia Sapriati (BIRCU, 2020)
The purpose of this study was to determine the differences in student learning outcomes in terms of student learning activities through the implementation of cooperative learning model Student Team Achievement Divisions (STAD) assisted by animation media and cooperative learning model type student team achievement divisions (STAD) assisted by power point media. This research will be conducted at SD Negeri 11 Rantau Selatan in Class VI the 2019/2020 Academic Year. The sampling technique uses purposive sampling, where researchers can determine samples based on specific objectives. The researcher determined that the sample in the study consisted of 2 classes, namely class VI a as a class of cooperative learning model type STAD assisted by animation media as many as 33 people, and class VI as many as 33 people as a class of cooperative learning model type STAD assisted by Power Point media. The instruments used were the Observation Sheet and the Test / Question Sheet. Measurements were made by Reliability, Distinguishing Power Analysis, Descriptive Data Analysis, Prerequisite Test Analysis, Two Ways ANOVA Hypothesis Test Analysis. The results of the study There are differences in learning outcomes in the sub-theme of Tumbuhan Sahabatku between those taught with the Cooperative Learning Model Type Student Team Achievement Division with animation aided with the Cooperative Learning Model Type Student Team Achievement Division assisted by Media Power Point in Class VI SD Negeri 11 Rantau Selatan, There are differences in results study of students who have high learning activities in the sub-theme of Tumbuhan Sahabatku, and there is an interaction between learning models and learning activities in influencing student learning outcomes in the sub-theme of Tumbuhan Sahabatku.